'From the wells': teaching openness in Judaism and Islam towards a shared society in Israel?. Issue 1 (2nd January 2022) - Agbaria, Ayman K.; Statman, Daniel
ABSTRACT: This article discusses the case study of a programme for Jewish and Palestinian educators in Israel and our initial insights into the outcome of the initiative. The programme aims to address racism, segregation, and prejudice and to support educators to teach culture and tradition in a more humanistic, inclusive, and critical way. To achieve this, it draws on inter-religious and intercultural dialogue. We will discuss how this method is rooted in both Judaism and Islam thus paving the way for participants to not only develop a better understanding of their own but also of others' tradition. Importantly, it also highlights the interrelations of these traditions, which can contribute to the development of a shared society.